Thrombocytopenia and endothelial dysfunction in hemorrhagic fever with renal syndrome - G. A. Mukhetdinova; R. M. Fazlyeva; D. A. Valishin; G. M. Khasanova; R. G. Yapparov (Журнал инфектологии, 2018)
Purpose: to estimate the content of platelets and sP-selectin in patients with different severity of Hemorrhagic Fever with Renal Syndrome. Materials and methods: we have conducted the clinical and laboratory examination of 220 patients with Hemorrhagic Fever with Renal Syndrome, including mild (52), moderate (112) and severe (56) forms. The quantitative content of sPselectin in blood serum was determined by enzyme immunoassay in 90 patients (30 people from each group). Results: during first days of admission to the hospital thrombocytopenia in patients with mild form of HFRS was moderate. For moderate and severe forms of HFRS during the initial period the average value of the platelet was less than 100u109/l; correlation analysis between platelet count and creatinine level revealed an inverse relationship between the platelet count during the initial period and the level of creatinine during the oliguric period (r=-0,526; p=0,029). The difference in the content of sP-selectin are statistically significant not only with the control group, but also between groups of patients depending on the severity of the disease, a correlation between the content of platelets and sP-selectin was revealed in all groups of patients. Conclusion: the activity of sP-selectin and the degree of thrombocytopenia are closely interrelated and characterize the severity of the disease.